2013
DOI: 10.1111/jpm.12074
|View full text |Cite
|
Sign up to set email alerts
|

Violent behaviour in a forensic psychiatric hospital in Finland: an analysis of violence incident reports

Abstract: The aim of this paper was to explore the frequency and provocation of physically violent incidents in a Finnish forensic psychiatric hospital. Three years (2007-2009) of violent incident reports were analysed retrospectively. The data were analysed by content analysis, and statistically by Poisson regression analysis. During the study period a total of 840 incidents of physical violence occurred. Six main categories were found to describe the provocation of violence where three of these categories seemed to be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 20 publications
(48 reference statements)
0
6
0
Order By: Relevance
“…In clinical practice, restrictive measures might partially prevent unwanted behaviours, but do not fully eliminate them, at least when used independently (Kuivalainen et al . ). This finding has also been reported with special observation (Stewart & Bowers ; Stewart et al .…”
Section: Introductionmentioning
confidence: 97%
“…In clinical practice, restrictive measures might partially prevent unwanted behaviours, but do not fully eliminate them, at least when used independently (Kuivalainen et al . ). This finding has also been reported with special observation (Stewart & Bowers ; Stewart et al .…”
Section: Introductionmentioning
confidence: 97%
“…Research in a forensic secure unit by Rutter, Gudjonsson and Rabe‐Hesketh () indicated that service users who had a greater tendency to engage in violence (>25 violent incidents over a period of 17 years) were more likely to be female, younger and to be on a civil section. A higher risk for females’ violent behaviour in forensic settings has been reported in several studies (Daffern, Mayer & Martin, ; Kuivalainen et al., ), with no specific explanations being offered. It has also been suggested that individuals who have been given a diagnosis of schizophrenia or personality disorder display greater levels of violence in secure hospitals than those without such diagnoses (Coid, Kahtan, Gault & Jarman, 1999; Rutter et al., ; Rylan, ) and that Caucasian service users are the aggressor in more incidents than non‐Caucasians (Dolan, Fullam, Logan & Davies, ).…”
Section: Factors Of Violence In Forensic and Psychiatric Settingsmentioning
confidence: 85%
“…In the United Kingdom (UK), almost half of the service users from a secure hospital were reported to have engaged in physical assaults over a 12‐month period (Novaco & Taylor, ), and a review from five secure USA services found that 31% of service users engaged in at least one violent assault over a year (Broderick, Azizian, Kornbluh & Warburton, ). In contrast, a study of a secure hospital in Finland revealed that only 17% of the service users had been violent over a 2‐year period (Kuivalainen, Vehvilainen‐Julkunen, Putkonen, Louheranta & Tiihonen, ). Violence in secure services results in longer periods of detention for service users, increases the risk of both harm to and burnout among staff, impairs treatment effectiveness, increases distress among service users and has important costs for the service in terms of staff members′ sick leave, compensation claims and employee turnover (Novaco & Taylor, ).…”
Section: Introductionmentioning
confidence: 99%
“…The second group comprises patients with psychotic disorders for whom treatment is particularly difficult or dangerous or simply not feasible in a local community hospital. The third group comprises those undergoing a forensic mental examination (Kuivalainen, Vehviläinen‐Julkunen, Putkonen, Louheranta, & Tiihonen, ). In addition to these two state mental hospitals, forensic psychiatric patients are treated on seven forensic psychiatric wards located in different hospital districts (Tenkanen, Tiihonen, Repo‐Tiihonen, & Kinnunen, ).…”
Section: Forensic Mental Health Nursing In Finlandmentioning
confidence: 99%